Impuesto federal a los sueldos generado por las microempresas: caso Cancún, México - Sergio Lagunas Pulsa; Miguel Angel Olivares Urbinaa; Natascha Tamara Post (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2012)
– The objective was given to identify which salary scales exist within micro-enterprises (SME's) of the economical sector depending on tourism, through representative sample taking, as well as determining the sector to which the SME's belong that generate greater revenue or, on the contrary, those that are largely subsidized by the government. The tax requirements for Mexican SME's are multiple. There is therefore a necessity for specific research and articles on this subject that can provide investors with elements of evaluation. The article focuses on Benito Juarez County, Quintana Roo, Mexico, home to tourist destination Cancún. The article begins with an outline of the importance of the SME's and a basis is established according to which we can consider SME's as being Mexican together with the origin of tax obligations. Furthermore a mechanism is introduced which calculates the federal tax fee on incomes, according to the main sectors a stratified sample of SME's is being determined, in accordance with the sample an estimation of revenue is made and finally the conclusions are presented. The presented information has added value as it constitutes a manual with regard to the payment of federal income tax generated in Mexico.
Keywords: H2; K3; M1; 650; taxations of micro-enterprises; tax contribution of wages and salaries; Cancun & tax contribution